PENGARUH PENGGUNAN MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) BERBANTU MULTIMEDIA INTERAKTIF TERHADAP HASIL BELAJAR EKONOMI - Kiki Melinda; Tiara Anggia Dewi (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This research was conducted with an effort to determine the effect of the use of CORE learning methods (Connecting, Organizing, Reflecting, Extending) assisted by interactive multimedia on student learning outcomes. CORE is learning that emphasizes students to be more active in finding information. So that with the presence of interactive multimedia can help students to find wider information.This research is the result of quantitative quasi-experimental research, with a design that is Non- equivalent Control Group Design. The selected sample is XI IPS 2 class with 27 students as the control class and XI IPS 1 as the experimental class with 31 students by using Purposive Sampling. Data collection methods by interview, documentation, observation and tests. Meanwhile, to determine whether there is an effect of the CORE method on social skills using the t-test formula. Based on the results of the study, through the calculation of the t-test formula the use of two similarity test levels with an average level of 5%. To test the hypothesis using the Simple Linear Registration formula Ỳ = a + bX is Ỳ = 39.44497 + 0.6424x followed by the tcount formula t = b / sb = 4.33. Ttab = 1,699 5% signification level to 4.33> 1,699, the hypothesis is accepted. So it can be concluded that there is a significant influence on the use of CORE Learning Methods (Connecting, Organizing, Reflecting, Extending) assisted by Interactive Multimedia on the learning outcomes of XI IPS MAN 1 Lampung Timur Economic Year 2019/2020